Method for producing grain-oriented electrical steel sheet

By performing laser irradiation with annular intensity distribution on the surface of the steel plate, the problem of the iron loss reduction effect disappearing after stress annealing in the prior art is solved, and the magnetic domain refinement effect without changing the magnetic flux density is achieved, and the insulation and floor area ratio are improved.

CN115917020BActive Publication Date: 2025-04-01JFE STEEL CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202180051593.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-08-27
Filing Date
2021-08-26
Publication Date
2025-04-01
Estimated Expiration
2041-08-26

AI Technical Summary

Technical Problem

The prior art is difficult to maintain the iron loss reduction effect after stress annealing, and magnetic domain refinement treatment can easily lead to a decrease in magnetic flux density and surface concave and convex formation, affecting insulation and floor area ratio.

Method used

By linearly irradiating laser light with an annular intensity distribution with a lower peripheral edge than the center on the surface of the steel plate integrated with Gaussian orientation, a magnetic domain refinement structure that does not change the magnetic flux density, and reduces iron loss.

Benefits of technology

The iron loss reduction effect is achieved after stress annealing, and the magnetic flux density is not changed, the surface concave and convex formation is avoided, and the insulation and floor area ratio are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004088157660000101
    Figure BDA0004088157660000101
Patent Text Reader

Abstract

The present invention proposes a method for manufacturing a grain-oriented electromagnetic steel sheet that controls a magnetic domain structure to reduce iron loss, in which the iron loss reduction effect can be maintained even when stress relief annealing is performed, and the magnetic flux density does not decrease after the magnetic domain control treatment. In the manufacturing method of the present invention, a laser having an annular intensity distribution with a lower intensity at the periphery than at the center is linearly irradiated on the surface of the grain-oriented electromagnetic steel sheet in a direction intersecting the rolling direction of the steel sheet.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing a low-iron-loss grain-oriented electromagnetic steel sheet suitable for an iron core material such as a transformer. Background Art

[0002] Grain-oriented electrical steel sheets are soft magnetic materials and are mainly used as core materials for transformers and rotating electrical machines. Therefore, grain-oriented electrical steel sheets are required to have magnetic properties with high magnetic flux density and low iron loss and magnetostriction. To meet this requirement, it is important to make the secondary recrystallized grains in the steel sheet highly uniform in the {100}<001> orientation (Goss orientation) or to reduce impurities in the product.

[0003] However, since there are limits to controlling crystal orientation and reducing impurities, a technology has been developed that physically introduces unevenness on the surface of a steel sheet to reduce the width of a magnetic domain and thereby reduce iron loss, namely, magnetic domain refining technology.

[0004] For example, Patent Document 1 proposes a technique for reducing iron loss by irradiating the final product sheet with laser light to introduce a linear high dislocation density region on the surface of the steel sheet. This technique has excellent manufacturability and is widely used, but there is an essential problem that the magnetic domain refinement effect disappears due to stress relief annealing. Therefore, in order to maintain the iron loss reduction effect, its use is limited to laminated core transformers that are not usually subjected to stress relief annealing.

[0005] On the other hand, a method for forming grooves mechanically using a toothed roller or the like (Patent Document 2) and a method for forming grooves by electrical or chemical means such as etching (Patent Document 3) have been developed. In this groove forming method, even when a heat treatment such as stress relief annealing is performed, the magnetic domain refinement effect does not disappear and the iron loss value is kept low, so it can be used as the core material of almost all transformers including wound core transformers. However, the former (Patent Document 2) has the problem of maintenance of worn toothed rollers, and the latter (Patent Document 3) has many manufacturing problems such as coating and removal of the resist ink used for etching and the problem of increased cost.

[0006] In contrast to these patent documents, Patent Document 4 proposes a technique for forming grooves on the final cold-rolled sheet using a laser or plasma flame, and maintaining the magnetic domain refinement effect even after stress relief annealing. However, since convex portions such as burrs are formed on the upper part of the groove wall surface simultaneously with the irradiation of the laser or plasma flame, there are problems such as reduced occupancy rate, reduced insulation of the coating applied thereafter, and transformer insulation breakdown, and so the technique has not yet been put into practical use.

[0007] In addition, no matter which method is used to refine the magnetic domains by forming grooves, the groove shape is prone to unevenness, and the obtained iron loss value is prone to deviation. In addition, since the actual cross-sectional area of ​​the steel plate is reduced in the groove forming part, the magnetic flux density is reduced by about 1% at most before and after the groove is formed.

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: Japanese Patent Publication No. 57-2252

[0011] Patent Document 2: Japanese Patent Publication No. 03-69968

[0012] Patent Document 3: Japanese Patent Application Laid-Open No. 61-117218

[0013] Patent Document 4: Japanese Patent Application Laid-Open No. 09-49024 Summary of the invention

[0014] The present invention has been developed in view of the above-mentioned current situation, and its object is to propose a method for manufacturing a grain-oriented electrical steel sheet in which the magnetic domain structure is controlled to reduce the iron loss, wherein the iron loss reduction effect can be maintained even when stress relief annealing is performed, and the magnetic flux density does not decrease after the magnetic domain control treatment.

[0015] The inventors have newly discovered that when the surface of a steel plate after secondary recrystallization with Gaussian orientation integration is subjected to linear laser irradiation in a direction intersecting the rolling direction of the steel plate (e.g., an orthogonal direction) to locally melt the irradiated area, a resolidified structure different from the original Gaussian orientation structure can be formed, and the magnetic domain refinement effect can be shown by the resolidified structure. Further research has confirmed that the so-called grooves are also formed according to the laser irradiation conditions, but when the resolidified structure is used for magnetic domain refinement, the formation of the grooves is not necessary for magnetic domain refinement. On the contrary, the grooves (recesses) cause the cross-sectional area of ​​the steel plate to decrease, and the magnetic flux density is also reduced, which has a great negative impact. In addition, if a groove is formed, a bulge of the excluded matrix iron, the so-called burr, is generated around the groove, which is also disadvantageous in terms of occupancy rate and insulation resistance.

[0016] Here, the resolidified structure is a structure in which the irradiated area is temporarily melted and solidified again by laser irradiation of the steel plate, thereby generating a solidified structure having an orientation different from the original crystal orientation before laser irradiation. Therefore, it is a structure different from the structure in which the original crystal orientation is maintained by rapidly heating and rapidly cooling by laser irradiation without melting the structure as in the conventional strain introduction type.

[0017] Based on the above insights, the inventors have repeatedly conducted in-depth research on the irradiation conditions of the laser that allows the matrix iron to efficiently absorb the incident energy of the laser and melt it while suppressing splashing. As a result, it was found that by irradiating the surface of the steel plate with a laser with an annular intensity distribution whose periphery is lower than the center, for example, a method of irradiating a laser with a strong center and a weak annular laser around the periphery, a molten portion can be formed on the surface of the steel plate without almost any unevenness, thereby being able to present a magnetic domain refinement effect without changing the magnetic flux density and reducing iron loss. It should be noted that if the energy intensity is different, lasers with different wavelengths can be combined. In addition, it is known that compared with the generally used YAG disk laser and optical fiber laser with a wavelength of about 1.0 μm, the green laser, UV laser, blue laser, etc. with a short wavelength have less reflection on the surface of the steel plate and are absorbed more efficiently, so it is easy to form a molten portion, which is effective in reducing the unevenness of the steel plate surface.

[0018] In the present invention, since the surface of the steel sheet after laser irradiation treatment is substantially free of irregularities, the reduction in magnetic flux density caused by the treatment is less than 0.2%. In addition, since the resolidified structure does not disappear even after stress relief annealing, the iron loss reduction effect brought about by the magnetic domain refinement treatment is maintained after stress relief annealing.

[0019] The main structure of the present invention is as follows.

[0020] (1) A method for producing a grain-oriented electrical steel sheet comprises irradiating a surface of the grain-oriented electrical steel sheet with a laser beam having an annular intensity distribution with a lower intensity at the periphery than at the center in a linear manner in a direction intersecting a rolling direction of the steel sheet.

[0021] (2) The method for producing a grain-oriented electrical steel sheet according to (1) above, wherein the wavelength of the laser light is 0.15 μm to 0.9 μm.

[0022] (3) The method for producing a grain-oriented electrical steel sheet according to (1) or (2) above, wherein the grain-oriented electrical steel sheet has a tension coating on the forsterite film.

[0023] According to the present invention, by subjecting the surface of a grain-oriented electrical steel sheet to a magnetic domain refining treatment by laser irradiation under appropriate conditions, it is possible to further reduce iron loss compared to the related art even after stress relief annealing. DETAILED DESCRIPTION

[0024] First, the development process of the present invention will be described.

[0025] First, if the view that the incident energy of the laser is efficiently absorbed by the matrix iron is established, the shorter the wavelength of the laser, the higher the energy, and the reflectivity on the surface of the steel sheet is reduced, so it is considered that it is effective to set the wavelength of the laser to be shorter than before. On the other hand, on the surface of the steel sheet after secondary recrystallization annealing of the grain group presenting the Gaussian orientation main body as the irradiation object of the laser, there is usually a forsterite film generated by the reaction of the annealing separator with MgO as the main body and the silicon oxide of SiO2 main body formed on the surface of the steel sheet before the secondary recrystallization. Therefore, the inventors and others irradiated the laser to the surface of the matrix iron through the forsterite film, realized efficient energy absorption on the surface of the matrix iron, and made the properties of the forsterite film required for the generation of a molten part with few bumps near the surface of the matrix iron. Here, forsterite itself is a transparent crystal, but it actually looks white, so it is believed that diffuse reflection of light occurs in the forsterite film due to the presence of grain boundaries. In other words, the thicker the forsterite film, the easier it is to absorb the energy of the laser. Therefore, in order to efficiently absorb the energy of the matrix iron, the thickness of the forsterite film is as thin as possible. Specifically, the weight per unit area is preferably set to 3.2 g / m 2 This is because the ratio of forsterite film is 3.2g / m 2 In the case of a thick layer, the energy of the laser beam may be higher, and the surface irregularities may become larger when the solidified structure is formed.

[0026] It should be noted that there are many methods for reducing the thickness of the forsterite film, but there is no particular limitation, and any method can be used. For example, forsterite itself is a composite oxide of Si and Mg, Mg2SiO4, so by reducing the dew point during decarburization annealing before secondary recrystallization annealing to reduce the amount of surface oxides of SiO2 as the main body, or reducing the hydration amount of the annealing separator mainly composed of MgO to reduce the reactivity, or reducing the coating amount of the annealing separator itself, or designing additives in the annealing separator, the forsterite film can be adjusted to 3.2 g / m 2 the following.

[0027] In addition, it is known that there is a technology for reducing iron loss by intentionally preventing or suppressing the formation of surface oxides such as forsterite film by smoothing the surface. For example, as a substitute for forsterite film, a technology for forming an extremely thin external SiO2 film, CVD film, PVD film can be cited. If the bending tightness and tension application effect can be ensured by the formation of these films, the unit area weight of the forsterite film can be greatly reduced, which is more preferred from the viewpoint of the laser energy absorption efficiency in the matrix iron of the present invention.

[0028] As a method for suppressing the formation of the forsterite film itself, there are known techniques such as lowering the dew point during decarburization annealing to suppress internal oxidation and form an extremely thin outer SiO2, adding chlorides etc. to the additive aid of the annealing separator, or changing the main component of the annealing separator itself to Al2O3 or CaO to prevent the forsterite film formation reaction from occurring.

[0029] Next, the preferred laser irradiation conditions are discussed. As magnetic domain refinement technologies using lasers, there are known strain introduction types that apply thermal strain to the surface of the steel plate to form a region with a very high dislocation density and narrow the magnetic domain width, and groove introduction types that directly form grooves on the surface of the base iron by high-energy laser irradiation, generate magnetic poles on the sides of the grooves, and narrow the magnetic domain width.

[0030] In contrast, the irradiation conditions of the laser of the present invention are between the two. That is, the resolidified structure obtained by locally melting the surface of the matrix iron by irradiating the laser has a crystal orientation different from the main Gaussian orientation of the secondary recrystallized grain group, so the resolidified structure produces a pseudo-grain boundary effect, which can narrow the magnetic domain width. Among them, if the irradiation energy of the laser is too large, the matrix iron on the surface of the steel plate evaporates or splashes to form grooves. Even if no grooves are formed, if a concave portion can be formed, a burr-like convex portion will be formed around it, thereby resulting in a reduction in the occupancy rate, or the insulating coating coated thereon becomes locally thinner, resulting in a reduction in insulation and corrosion resistance. Therefore, it is preferred to form an irradiation condition in which grooves and concave-convex portions are not formed as much as possible in the irradiated portion of the laser.

[0031] In order to avoid forming unevenness in the laser irradiation part and to efficiently melt the matrix iron locally, it is effective to use lasers with different intensities. Specifically, if the laser is irradiated in a concentric circle, the expansion of evaporation and splashing of the matrix iron can be suppressed by strengthening the intensity of the central laser and weakening the intensity of the peripheral laser, so that only the central part can be efficiently melted. As a method of setting the irradiation energy difference between the center and the periphery of the laser, in addition to changing the energy density of the laser, it is also effective to use lasers with different wavelengths. For example, a high-intensity laser is irradiated to the center as the main beam, and the focus is adjusted around it to diffuse it, and a ring-shaped low-intensity laser is generated as a side beam, so that a laser with a ring-shaped intensity distribution with a lower periphery than the center can be obtained. The wavelength of the side beam can be the same as or different from that of the main beam. As long as the desired intensity distribution is obtained at the irradiation position, one of the transverse mode lasers such as the ring mode can be used alone, or two or more different types of transverse mode lasers can be used in combination. Here, it is difficult to limit the energy range of the laser on the high energy side and the low energy side, but it is preferable to select a combination of lasers with an energy range that forms a molten portion on the surface of the steel plate (base iron) and has a surface unevenness difference of less than 3 μm.

[0032] It should be noted that regarding the wavelength of the laser, the shorter the wavelength, the higher the energy, the less reflection on the surface of the material, and the better the absorption into the material. Specifically, by using a laser with a wavelength of 0.9 μm or less, the reflectivity decreases and the absorptivity increases, so it is possible to form a local melt while suppressing splashing. When the laser irradiation technology is applied to a steel plate that suppresses the formation of a forsterite film or has been subjected to a mirror finish treatment, a laser with a short wavelength is more effective. Considering the constraints on the equipment, the lower limit of the wavelength of the laser is preferably 0.15 μm.

[0033] For example, since it is easy to focus laser light more finely, the wavelength of the widely used YAG laser is 1.03 to 1.07 μm, but the second harmonic is half the wavelength of the green laser of 0.53 μm, and the third and fourth harmonic wavelengths of UV laser are 0.36 μm and 0.27 μm respectively. They have good absorption efficiency and are not easy to splash, so they are more advantageous from the perspective of maintaining surface flatness. Similarly, blue lasers with wavelengths of 0.44 to 0.49 μm using blue semiconductors, etc., and excimer lasers with wavelengths of 0.19 to 0.31 μm using halogen gases are also effective.

[0034] On the other hand, in a general laser with a wavelength of about 1 μm, if the steel plate surface is a mirror surface and light is easily reflected, the laser light is reflected, and the matrix iron (inside the steel plate) absorbs energy, making it very difficult to form a local melt portion.

[0035] Since the laser output is a combination of two or more lasers with different intensities, it is difficult to define appropriate conditions, but the total heat per unit length is preferably 2 J / m to 50 J / m, and the spot diameter of the laser beam is preferably 100 μm or less. The above spot diameter refers to the longest diameter of the irradiation shape formed by the high-intensity laser in the center and the ring-shaped low-intensity laser in the periphery.

[0036] The molten region near the surface of the steel sheet formed by the laser has a width of 20 to 200 μm and a depth of 2 to 50 μm, and the repetition interval in the rolling direction is preferably 0.5 mm to 20 mm.

[0037] In the present invention, the laser irradiation "linearly" includes not only solid lines but also dot-dash lines, broken lines, etc. In addition, "a direction intersecting the rolling direction" refers to an angle range within ±30° relative to a direction perpendicular to the rolling direction.

[0038] The magnetic domain refinement effect of the linear molten zone formed by the laser is integrated into the orientation of the grains after the secondary recrystallization, which is the easy axis of magnetization. <100> Therefore, the higher the B8 value, which is an indicator of the integration, the greater the iron loss reduction effect caused by the laser. Therefore, in the present invention, the steel plate to be irradiated preferably has a magnetic flux density B8 of 1.90T or more. In addition, the present invention makes use of the magnetic domain refinement technology of the melt resolidification structure obtained by single-sided laser irradiation, and its effect is limited if the steel plate is thick. Therefore, the target plate thickness is preferably 0.23mm or less.

[0039] Preferred production conditions of the present invention are described below.

[0040] First, the preferred composition of the material is described. The composition of the material can be appropriately determined based on the compositions of various grain-oriented electrical steel sheets known in the past to produce secondary recrystallization and obtain a composition of B8:1.90T or higher. The composition specifically described below is only an example and is not limited thereto.

[0041] In the manufacture of the grain-oriented electrical steel sheet of the present invention, when an inhibitor is used, for example, when an AlN-based inhibitor is used, the component composition may contain Al and N in appropriate amounts, and when a MnS·MnSe-based inhibitor is used, Mn, Se and / or S in appropriate amounts. Of course, two inhibitors may be used in combination. In this case, the preferred contents of Al, N, S and Se are respectively Al: 0.01 to 0.065 mass%, N: 0.005 to 0.012 mass%, S: 0.005 to 0.03 mass%, and Se: 0.005 to 0.03 mass%.

[0042] In addition, the present invention can also be applied to a grain-oriented electrical steel sheet in which the contents of Al, N, S, and Se are limited and no inhibitor is used. In this case, the contents of Al, N, S, and Se are preferably suppressed to Al: 100 mass ppm or less, N: 50 mass ppm or less, S: 50 mass ppm or less, and Se: 50 mass ppm or less, respectively.

[0043] If other essential components and optional added components are discussed, they are as follows.

[0044] C: 0.08 mass % or less

[0045] If the amount of C exceeds 0.08 mass %, the burden in the manufacturing process increases in order to reduce C to less than 50 mass ppm at which magnetic aging does not occur. Therefore, it is preferably less than 0.08 mass %. It should be noted that, with respect to the lower limit, even if the material does not contain C, secondary recrystallization can be performed, and no special setting is required, and it can be 0 mass %.

[0046] Si: 2.0-8.0 mass%

[0047] Si is an element that is effective in increasing the resistance of steel and improving iron loss. When the content is 2.0 mass % or more, the iron loss reduction effect is particularly good. On the other hand, when it is 8.0 mass % or less, particularly excellent workability and magnetic flux density can be obtained. Therefore, the Si content is preferably in the range of 2.0 to 8.0 mass %.

[0048] Mn: 0.005-1.0 mass%

[0049] Mn is an element that is beneficial in improving hot workability, but the addition effect is insufficient when the content is less than 0.005 mass%. On the other hand, if the content is set to 1.0 mass% or less, the magnetic flux density of the product sheet is particularly good. Therefore, the Mn content is preferably in the range of 0.005 to 1.0 mass%.

[0050] In addition to the above-mentioned basic components, the following elements may be appropriately contained as arbitrary magnetic property improving components.

[0051] At least one selected from the group consisting of Ni: 0.03-1.50 mass%, Sn: 0.01-1.50 mass%, Sb: 0.005-1.50 mass%, Cu: 0.03-3.0 mass%, P: 0.02-0.50 mass%, Mo: 0.005-0.10 mass%, and Cr: 0.03-1.50 mass%

[0052] Ni is an element useful for improving the hot-rolled sheet structure and further improving the magnetic properties. However, if the content is less than 0.03 mass%, the effect of improving the magnetic properties is small. On the other hand, when it is less than 1.50 mass%, the stability of the secondary recrystallization is increased, and the magnetic properties are improved. Therefore, the Ni content is preferably in the range of 0.03 to 1.50 mass%.

[0053] In addition, Sn, Sb, Cu, P, Cr and Mo are elements useful for improving magnetic properties, but when each does not meet the lower limit of each component mentioned above, the effect of improving magnetic properties is small. On the other hand, when the upper limit of each component mentioned above is below, the development of secondary recrystallized grains is the best. Therefore, it is preferably contained in the above range.

[0054] It should be noted that the remainder other than the above-mentioned components is inevitable impurities and Fe mixed in during the production process.

[0055] In the present invention, the process of manufacturing the grain-oriented electrical steel sheet can basically follow a conventionally known manufacturing process.

[0056] The steel billet material adjusted to the above-mentioned suitable component composition can be made into a slab by the usual ingot casting method or continuous casting method, or a thin cast sheet with a thickness of less than 100 mm can be directly manufactured by the continuous casting method. The slab can be heated by the usual method and supplied to hot rolling, but it can also be supplied to hot rolling immediately after casting without heating. In the case of thin cast sheets, hot rolling can be performed, or hot rolling can be omitted and the subsequent process can be directly entered. As a suitable condition, after annealing the hot-rolled sheet as needed, it is made into the final plate thickness by cold rolling once or more than two cold rollings separated by intermediate annealing. Then, after decarburization annealing, an annealing separator with MgO as the main component is applied, and then a final annealing is performed, and a tension coating is performed as needed to make a product.

[0057] As the tension coating, a known tension film, for example, a glass coating mainly composed of phosphate such as magnesium phosphate and aluminum phosphate and a low thermal expansion oxide such as colloidal silica, etc. can be applied.

[0058] In the present invention, during the final annealing, any of the various film thickness adjustment methods described above can be used to make the weight per unit area of ​​the forsterite film formed on the surface of the steel sheet preferably 3.2 g / m 2 As a method for actively suppressing the formation of forsterite film, the dew point during decarburization annealing can be lowered, or the formation of surface oxides of SiO2 as a main body can be suppressed as a non-decarburization atmosphere, or chlorides can be added to the additives of the annealing separator, or the main component of the annealing separator itself can be changed to Al2O3, CaO to prevent the formation reaction of forsterite film.

[0059] Example

[0060] A steel billet having a composition containing C: 0.055 mass% (550 mass ppm), Si: 3.40 mass%, Mn: 0.30 mass%, Al: 0.017 mass% (170 mass ppm), S: 0.0015 mass% (15 mass ppm), Se: 0.010 mass% (100 mass ppm), N: 0.006 mass% (60 mass ppm), P: 0.06 mass%, Sb: 0.07 mass%, Mo: 0.015 mass%, and the balance being Fe and inevitable impurities was heated to 1350°C, hot rolled to a thickness of 2.2 mm, annealed at 1050°C for 30 seconds for hot rolled sheet, and cold rolled once using a tandem mill to obtain a cold rolled sheet having a final sheet thickness of 0.23 mm. Then, the steel billet was heated to 820°C and decarburized for 1 minute and 10 seconds in a wet hydrogen atmosphere. Next, an annealing separator composed mainly of magnesium oxide is applied to the steel sheet after decarburization annealing. The annealing separator uses MgO as the main agent and various amounts of TiO2 added as an auxiliary agent. In addition, for some materials, Sb chloride is added to the annealing separator to suppress (reduce) the formation of forsterite film. Then, a final annealing is performed at 1200°C for the purpose of secondary recrystallization and forsterite film formation and purification.

[0061] The magnetic properties (iron loss W 17 / 50 ), the steel plate is irradiated with the following laser: a continuously oscillating fiber laser is used as the main beam to irradiate the center, and at the same time, the focus of the sub-beams of the same wavelength are adjusted around it to diffuse, thereby generating a ring-shaped laser with different intensity distributions of the main beam in the center and the ring-shaped sub-beams in the periphery. Specifically, the laser beam is irradiated linearly in a direction perpendicular to the rolling direction at a scanning speed of 1000 mm / sec and an irradiation interval of 5 mm in the rolling direction of the steel plate. At this time, the output of the main beam and the surrounding sub-beams are variously changed. In addition, the material after laser irradiation is coated with an insulating coating composed of 50% colloidal silica and magnesium phosphate, and a sintered tension coating treatment is performed. In addition, for some conditions, laser irradiation treatment is performed after tension coating.

[0062] Table 1 shows the weight per unit area of ​​the forsterite film of the steel plate sample thus obtained, the amount of unevenness of the flatness near the laser irradiation measured by cross-sectional observation, and the magnetic properties (iron loss W 17 / 50) and the laser irradiation conditions. It should be noted that the weight per unit area is the difference in mass before and after the forsterite film is removed using a high-temperature, high-concentration NaOH solution. The amount of unevenness is the difference between the highest point and the lowest point of the cross section near the irradiated portion measured from the surface using a three-dimensional laser displacement meter. In addition, the magnetic properties are measured according to the iron loss test method (Epstein test). For the sub-beam irradiation conditions in Table 1, "weak surrounding" refers to the case where the intensity of the annular peripheral sub-beam is set to a desired intensity distribution that is lower than the intensity of the main beam at the center. On the other hand, "none" refers to the case where the annular peripheral sub-beam is not irradiated, and "strong surrounding" refers to the case where the intensity of the annular peripheral sub-beam is set to be higher than the intensity of the main beam at the center. In addition, the width of the molten portion is measured using a three-dimensional laser displacement meter.

[0063] It should be noted that the width of the molten zone can usually be measured using a three-dimensional laser displacement meter. If a judgment is desired, the elastic strain of the cross section near the irradiated portion can be measured by comparison using the EBSD (Electron Back Scattering Diffraction pattern) method, or it can be measured based on the discontinuous position of the magnetic domain structure using a magnet observer.

[0064]

[0065] As shown in Table 1, the unit area weight of the forsterite film is 3.2 g / m 2 When the following electromagnetic steel sheets were irradiated with laser beams of different energy densities in appropriate combination (inventive examples), extremely low iron loss values ​​were obtained and a flat surface without burrs was obtained near the irradiated portion.

[0066] In addition, as shown in No. 5 and No. 10, when a material having a smooth surface with a forsterite film formed is used, the iron loss is significantly improved (reduced) by using the present invention. In addition, by shortening the wavelength of the laser, a trend is seen in which the height of the generated burrs (the amount of unevenness) becomes relatively smaller.

Claims

1. A method for manufacturing a oriented electrical steel sheet having a unit area weight of 3.2 g / m 2 The surface of the oriented electromagnetic steel sheet with the following forsterite coating is linearly irradiated with laser within an angle range of ±30° relative to the rolling direction of the steel sheet, so that the matrix iron surface is locally melted to form a resolidified structure having a crystal orientation different from the main Gaussian orientation of the secondary recrystallized grain group, and the laser has an annular intensity distribution with lower intensity at the periphery than at the center.

2. The method for producing a grain-oriented electrical steel sheet according to claim 1, wherein: The wavelength of the laser is 0.15 μm to 0.9 μm.

3. The method for producing a grain-oriented electrical steel sheet according to claim 1 or 2, wherein: The grain-oriented electrical steel sheet has a tension coating on a forsterite film.

Citation Information

Patent Citations

  • Improving method for iron loss characteristic of directional electrical steel sheet

    JP1982002252B2

  • Manufacture of grain oriented magnetic steel sheet of low iron loss

    JP1986117218A

  • Manufacture of single-oriented electromagnetic steel sheet having low iron loss

    JP1991069968B2

  • Production of grain oriented silicon steel sheet with low iron loss

    JP1997049024A

  • Laser processing apparatus and laser irradiation method

    US20150318091A1